Freshness Evaluation of Minced Fish (Snakehead, Spotted Mackerel, Snapper, and Sardine) Sold at a Traditional Market in Palembang Using Chemical, Physical, Microbiological, and Sensory Parameters - Riya Liuhartana Nasyiruddin Fuhrmann; Rih Laksmi Utpalasari; Lia Perwita Sari; Zhulian Hikmah Hasibuan; Widyawati; Melia Oktariani; Sohail Khan (International Journal of Food Sciences and Nutrition Innovations, 2025)
Background: Minced fish is widely marketed in traditional markets due to its practical use as raw material for various processed fish products. However, mechanical mincing under inadequate hygiene and cold-chain management may lead to an increase in Total Plate Count (TPC), thereby accelerating quality deterioration and increasing potential food safety risks.Objective: This study evaluated the freshness and quality of minced fish sold in a traditional market using integrated chemical, physical, microbiological, and sensory indicators.Methods: A purposive sampling approach was applied to four types of minced fish sold at Perumnas Sako Kenten Market, Palembang: snakehead (Channa striata, S1), spotted mackerel (Scomberomorus guttatus, S2), snapper (Lutjanus campechanus, S3), and sardine (Sardinella lemuru, S4). Analyses included proximate composition, pH, Total Volatile Base Nitrogen (TVB-N), Trimethylamine Nitrogen (TMA-N), Total Plate Count (TPC), descriptive sensory scoring, and hedonic evaluation. Results were interpreted descriptively and compared with Indonesian National Standards (SNI) and relevant literature.Results: All samples exhibited TPC values exceeding the SNI limit (1×10⁶ CFU/g), ranging from 1.6×10⁷ to 2.8×10⁷ CFU/g. TVB-N values remained low (6.0–7.6 mgN/100 g), while elevated TMA-N levels were observed in spotted mackerel and sardine, indicating reduced freshness in pelagic species. Sensory evaluation showed good acceptance for snakehead, spotted mackerel, and snapper, whereas sardine received neutral to low scores, particularly for aroma and texture.Conclusion: The quality of minced fish varied among species, while microbial contamination consistently exceeded safety limits. Sensory evaluation remains important but insufficient alone; therefore, integrated freshness assessment supported by improved hygiene and cold-chain management is essential.